Penyuluhan Hukum Strategi Advokat dalam Menangani Perkara Tindak Pidana Korupsi - Fathur Rauzi; Kamil, Muhammad Ikhsan (Insan Kreasi Media, 2023)
Corruption is an extraordinary crime that not only harms the country but also causes poverty and underdevelopment of some Indonesian people because their needs are not met. In handling corruption cases, an advocate has the role of representing clients and at the same time acting as legal adviser and defender of suspects or defendants. The purpose of carrying out this service activity is to provide understanding to prospective advocates, especially prospective advocates from the West Nusa Tenggara Indonesian Advocates Association regarding how to set strategies as advocates in dealing with Corruption Crime cases. The results of this service activity received a positive response from the training participants, the DPD IKADIN NTB and the dean of the UIN Mataram Sharia Faculty. This form of positive response was seen, among other things, from the active participation, both from the Institute and from the training participants. When providing legal assistance to a client who commits TIPIKOR, an Advocate must be guided by the Indonesian Advocate Code of Ethics and the Advocate Law and other laws and regulations governing Advocates. The arrangement aims to ensure that the Advocate's role in defending remains based on truth and justice.